Scotty, sage of Sagada - Schlegel, Stuart A. (Philippine studies : historical and ethnographic viewpoints, 2017)
"These reminiscences are personal experiences and anecdotes drawn from my decades-long close relationship with William Henry Scott (1921-1993), an Episcopal lay missionary in the Philippines who was famous in that land as a world-class historian and scholar, a prominent voice against the Marcos dictatorship, and one of the most unusual personalities that could be imagined."